CORPORATE SOCIAL RESPONSIBILITY AUTHENTICITY AND FIRM PERFORMANCE IN AN EMERGING MARKET - Le, Thanh Tiep (Trường Đại học Đà Lạt, 2024)
This study uses quantitative methods to investigate the importance of corporate social responsibility authenticity (CSRA) on the performance of small and medium-sized enterprises (SMEs). It investigates the interceding roles of organizational identification (OID) and corporate reputation (CRE) between CSRA and firm performance (FPE). The data, which were questionnaire responses from 548 customers, employees, and shareholders of SMEs, were analyzed using SmartPLS version 3.3.2. Significant positive correlations were found between the authenticity of corporate social responsibility (CSR) and three key factors: firm performance, organizational identification, and corporate reputation. This study contributes to existing knowledge by exploring the mediating roles of OID and CRE in the relationship between CSRA and FPE. To better understand how CSR affects OID, CRE, and eventually FPE, this study integrates the perceptions of internal and external stakeholders on the degree to which CSR is seen as authentic. This study particularly adds to the body of CSR literature in the context of increasing skepticism of stakeholders about CSR authenticity. Grounded in stakeholder behaviors, social identity, and social exchange theories, this study extends these theories by operationalizing a novel empirical framework in a new setting. Furthermore, the implications of this study extend to society’s current concerns about “greenwashing” or “corporate hypocrisy.”